Cholesterol-Lowering Effects of Turmeric Effervescent Dosage in Preventing Atherosclerosis - Pomalango, Zulkifli B.; Paneo, Mohamad Aprianto; Pakaya, Nasrun; Aman, La Ode; Hutuba, Ariani H. (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
This study aims to evaluate the cholesterol-lowering effects of turmeric (Curcuma domestica) in an effervescent powder drink formulation to prevent atherosclerosis. The effervescent preparation was produced using standard effervescent techniques, with organoleptic tests revealing an orange color, the characteristic aroma of turmeric, and a slightly sweet taste. The formulation’s pH was approximately 5.9, with a flowability test result of 14 seconds, a powder angle of repose of 30°, and a dissolution time of 4 minutes and 20 seconds. Curcumin shows potential as an anticholesterol as a preventive measure of atherosclerosis disease through molecular docking testing using autodock-vina. Qualitative test on turmeric effervescent with Sprektrofotometer UV-VIS, Scanning Electon Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). Cholesterol testing was conducted on mice induced with cholesterol using margarine over a one-week period, resulting in increased cholesterol levels of maximum 290 mg/dL. Following administration of the converted turmeric dosage, cholesterol levels significantly maximum decreased in the first week to 165 mg/dL. By the second week, further reductions were observed, with cholesterol levels maximum dropping to 143 mg/dL. These results suggest that turmeric effervescent formulation exhibits promising cholesterol-lowering properties and may contribute to the prevention of atherosclerosis